ANALISIS PERILAKU BULLYING TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR: ANALYSIS OF BULLYING BEHAVIOR ON ELEMENTARY SCHOOL STUDENTS' LEARNING MOTIVATION - Candrawati, Riska; Setyawan, Agung (CV. Kalimasada Group, 2023)
This study was conducted with the aim of understanding (1) the types of bullying that occur at SDN Tanjung Jati 2 Kamal, (2) the impact of bullying on student learning motivation at SDN Tanjung Jati 2 Kamal, and (3) what contributions have been made by the school in handling bullying. This research uses a qualitative research method with a field research approach. Researchers went directly to the field to collect the necessary data. Data collection techniques include observation, interviews, and documentation. The collected data were then analyzed through data reduction, data presentation, and data conclusion/verification. The results of this study show that bullying that often occurs at SDN Tanjung Jati 2 Kamal includes physical bullying, verbal bullying, and mental bullying. Physical bullying involves acts of physical violence against students, such as punches or kicks. Verbal bullying includes verbal insults, taunts or threats. Mental bullying involves acts of intimidation, isolation, or social rejection that impact on students' emotional well-being. Based on the research results, it can be concluded that bullying has a negative impact on student learning motivation at SDN Tanjung Jati 2 Kamal. Students who are victims of bullying tend to experience decreased learning motivation, anxiety, and emotional disturbance. In addition, this study also revealed that the school has done a lot to prevent bullying.